MODERN APPROACHES TO TECHNICAL TRAINING: A COMPARATIVE STUDY OF RUGBY AND HANDBALL - POP, Sergiu (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
This study compares modern technical-training approaches in rugby and handball by implementing a 6-week, sport-specific training intervention with university-level athletes (n = 20; 10 rugby, 10 handball). Training emphasized sport-specific technical drills, feedback (video and verbal), and progressive overload within a periodized microcycle structure. Outcome measures (pre/post) were: passing/throwing accuracy (% successful hits on a 1-m² target at 10 m, 10 trials), simple reaction time (ms, digital light system), and a composite Coordination Index (CI) derived from agility + dual-task accuracy tests. Both groups trained 3×/week (90 min/session). Paired-sample analyses showed statistically significant improvements across all measures in both groups. Handball players improved more on throwing accuracy (Δ = +15.3%, t(9) = 6.93, p < .001, Cohen’s d ≈ 2.19) while rugby players showed strong gains in coordination and tactical synchronization (Coordination Index Δ = +1.20, t(9) = 4.44, p = .0016, d ≈ 1.40). Reaction time improved in both groups (rugby Δ = –37 ms, p = .003; handball Δ = –42 ms, p < .001). Results support integrating periodized technical work, feedback-rich practice, and scenario-based drills to optimize skill transfer; practical implications for coaches include microcycle examples, video-feedback timing, and objective monitoring.